2020
DOI: 10.3390/biom11010013
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-Derived Plant Protection Metabolite 2,4-Diacetylphloroglucinol: Effects on Bacterial Cells at Inhibitory and Subinhibitory Concentrations

Abstract: 2,4-Diacetylphloroglucinol (2,4-DAPG) is a well-known bacterial secondary metabolite, however, its mechanism of inhibitory and subinhibitory action on bacterial cells is still poorly understood. The mechanism of 2,4-DAPG action on model bacterial strains was investigated using fluorescent spectroscopy and the action of the antibiotic was found to involve a rapid increase in membrane permeability that was accompanied by a reduction in its viability in nutrient-poor medium. At the same time, antibacterial action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Our genomic analyses and metabolic analyses on strain XL17 and previous studies on potent biocontrol pseudomonads [69,73,74], including strains Pf275 and 2P24 [65,68], strongly suggest that DAPG and lipopeptides are the key antimicrobial metabolites from strain XL17 to breach the cell envelopes of Psa and B. cinerea. On the other hand, DAPG and cyclic lipopeptides produced by plant-associated pseudomonads [73][74][75][76][77] may be toxic to plants [74,78]. Thus, we did a phytotoxic test and demonstrated that strain XL17 and its CF were not toxic to rice seeds and seedlings but increased rice shoot height and dry weight.…”
Section: Strain Xl17 Produced Iaa and Acc Deaminasementioning
confidence: 90%
“…Our genomic analyses and metabolic analyses on strain XL17 and previous studies on potent biocontrol pseudomonads [69,73,74], including strains Pf275 and 2P24 [65,68], strongly suggest that DAPG and lipopeptides are the key antimicrobial metabolites from strain XL17 to breach the cell envelopes of Psa and B. cinerea. On the other hand, DAPG and cyclic lipopeptides produced by plant-associated pseudomonads [73][74][75][76][77] may be toxic to plants [74,78]. Thus, we did a phytotoxic test and demonstrated that strain XL17 and its CF were not toxic to rice seeds and seedlings but increased rice shoot height and dry weight.…”
Section: Strain Xl17 Produced Iaa and Acc Deaminasementioning
confidence: 90%
“…As reported in [46], intracellular targets of 2,4-diacetylphloroglucinol action were assessed using bacterial biosensors with inducible bioluminescence corresponding to DNA and protein damage. However, unlike our study, it was not possible to register a positive response from any biosensor.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike our study, it was not possible to register a positive response from any biosensor. As a result, the bactericidal effect of 2,4-DAPG is believed to be related to the destruction of bacterial barrier structures [46].…”
Section: Discussionmentioning
confidence: 99%
“…DAPG exhibits high antimicrobial activity against several bacteria, including the Gram-positive model Bacillus subtilis and the Gram-negative plant pathogen Pseudomonas syringae [13]. Conversely, it is quite inefficient against Pseudomonas aeruginosa and Pseudomonas fluorescens strains [13,111]. This discrepancy could originate from differential membrane permeability and/or the presence of detoxifying efflux pumps.…”
Section: Direct Inhibition Of Soil-borne Plant Pathogensmentioning
confidence: 99%
“…This discrepancy could originate from differential membrane permeability and/or the presence of detoxifying efflux pumps. It has been proposed that DAPG targets the bacterial envelop [111], but little is known about the mode of action of DAPG towards bacteria. At subinhibitory concentrations, DAPG has been shown to reduce biofilm and spore formation in B. subtilis [112].…”
Section: Direct Inhibition Of Soil-borne Plant Pathogensmentioning
confidence: 99%